Comparison of conservative and surgical therapy concepts for synechia of the labia in pre-pubertal girls = Vergleich konservativer und operativer Therapiekonzepte der Labiensynechie präpubertaler Mädchen - Bussen, Stefanie; Sütterlin, Marc (Geburtshilfe und Frauenheilkunde, 2016)
Introduction: The aim of this study was to evaluate the primary and secondary therapeutic successes of different therapy schemes for the treatment of synechia of the labia in pre-pubertal girls. Materials and Methods: The treatment courses of 47 pre-pubertal girls who were treated between February 2007 and February 2013 in the special outpatient clinic for paediatric gynaecology of a department for gynaecology at a German university hospital and for whom information on the course of the disease was available for at least the six months following end of the treatment. 23 of these children were treated with a topical estriol therapy (treatment group A). For 24 of the girls a manual separation of the adhering labia minora was undertaken (treatment group B). Statistical evaluation was performed using the x2 test, Fischerʼs exact test and the Mann-Whitney U test. Results: For 18 of the 23 (80 %) girls in treatment group A topical estriol therapy alone led to a resolution of the synechia. Five of these 23 children (20 %) required a secondary manual separation. All girls for whom treatment was not successful were under 5 years of age. For all 24 girls (100 %) of treatment group B the primary manual separation was performed with success. The recurrence rates after ≥ 6 months in cases with identical after-care did not differ between the two treatment groups (treatment group A: 34 %, treatment group B: 33 %, x2 test: p = 0.853). 16 of the 17 recurrences occurred ≥ 3 months after the end of the therapy. Conclusion: Our results show that for children < 5 years of age a 4-week topical therapy with estriol is a promising therapy option for synechia of the labia that is less of a burden for the family situation. Especially for girls ≥ 5 years of age, primary therapy fails in up to 20 % of the cases. Primary manual separation represents a more effective therapeutic option. Irrespective of the treatment applied, a recurrence after ≥ 3 must be expected in one-third of the treated girls.
Gesehen am 02.04.2019